2020
DOI: 10.1016/j.envpol.2020.115148
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter (PM10) enhances RNA virus infection through modulation of innate immune responses

Abstract: Sensing of pathogens by specialized receptors is the hallmark of the innate immunity. Innate immune response also mounts a defense response against various allergens and pollutants including particulate matter present in the atmosphere. Air pollution has been included as the top threat to global health declared by WHO which aims to cover more than three billion people against health emergencies from 2019 to 2023. Particulate matter (PM), one of the major components of air pollution, is a significant risk facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 158 publications
4
35
0
Order By: Relevance
“…TLRs are representative PRRs that play pivotal roles in innate immune responses to infection in epithelial cells and phagocytes. The mechanisms involved in PM-induced innate immune responses are mainly through the production of proinflammatory cytokines and chemokines via activation of the TLR signaling pathway [1,66,67]. There is ample evidence demonstrating that PM modulates cytokine and chemokine levels, although the effects vary depending on the airway exposure regime [61,68].…”
Section: Mucosal Exposure and Innate Immune Responses To Pm Innate Immentioning
confidence: 99%
See 2 more Smart Citations
“…TLRs are representative PRRs that play pivotal roles in innate immune responses to infection in epithelial cells and phagocytes. The mechanisms involved in PM-induced innate immune responses are mainly through the production of proinflammatory cytokines and chemokines via activation of the TLR signaling pathway [1,66,67]. There is ample evidence demonstrating that PM modulates cytokine and chemokine levels, although the effects vary depending on the airway exposure regime [61,68].…”
Section: Mucosal Exposure and Innate Immune Responses To Pm Innate Immentioning
confidence: 99%
“…Further studies are required to clarify specific components of the PM mixture that activate PRR signaling during early innate immunity and proinflammatory responses (Figure 1). pathway [1,66,67]. There is ample evidence demonstrating that PM modulates cytokine and chemokine levels, although the effects vary depending on the airway exposure regime [61,68].…”
Section: Mucosal Exposure and Innate Immune Responses To Pm Innate Immentioning
confidence: 99%
See 1 more Smart Citation
“…Non-treated wastewaters will increase the incidence and prevalence of new cases of COVID-19 disease in a community that occurs in a specified period and a specified point in the time respectively [28]. As you can see in the curve, according to official statistics, the number of new patients has been increasing despite the ups and downs.…”
Section: Theoretical Explorationmentioning
confidence: 99%
“…Indoor aerosol exposure can also aggravate the symptoms of infection in COVID-19 patients. Mishra et al ( 2020 ) reported that exposure to particulate matter could promote the replication of RNA viruses by suppressing the antiviral innate immune response. Zhou et al ( 2020 ) conducted a comprehensive analysis of 30 immunological indicators in the blood of COVID-19 patients ( n =33) and elucidated the key mechanism of severe pneumonia cytokine storm caused by SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%